PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN METODE OK5R PADA SISWA KELAS IV SD - Wulandari, Iis (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to describe the improvement of reading comprehension skill of the 4th-grade students of Elementary School No.08 Padang Besi,Padang with the use of OK5R method. This study is classroom action research that uses qualitative and quantitative approaches. The result showed that students’ reading comprehension ability increased from 70,5 (Fair) with 70,5% level of mastery in cycle I, to 86,3 (Very good) with 86% level of mastery in cycle II. The percentage of improvement from cycle I to cycle II is 16%. Based on these results, it is concluded that OK5R methodsignificantly improves the reading comprehension ability of the 4th-grade students of Elementary School No.08 Padang Besi, Padang.